Multicore fibers for sensing applications - Zhang, Hailiang (2018)
Multicore fibers (MCFs) are optical fibers which have several cores integrated into a common cladding. As one type of space-division multiplexing, MCFs have been widely investigated in optical communication to improve the data capacity limit. Due to the intrinsic advantages such as small size, well-defined core separation, improved isothermal behaviour, light weight, immunity to electromagnetic interference, MCFs have also attracted extensive interests for optical sensing applications. This thesis focuses on investigating and fabricating MCF-based sensors with high performances by post-processing techniques such as inscribing gratings or introducing helical structures into the MCFs. In this thesis, we first review the background knowledge and development of MCF-based sensors. And then we detail the working principles, fabrication methods and experimental results of three sensors based on a heterogeneous MCF. The first one is a directional bending sensor based on a heterogeneous MCF with fiber Bragg gratings (FBGs). To date, several types of sensors based on FBGs inscribed in homogeneous MCFs have been reported. However, due to the homogeneous properties of the multiple cores, simultaneous interrogation of the FBGs in the multiple cores demands high precision and cumbersome alignment with, for example, a coupler and a ball lens, or customized and complicated fan-out devices. Therefore, to realize an easier interrogation of the FBGs in different cores, we propose to inscribe FBGs in heterogeneous MCFs. As the heterogeneous MCFs have non-identical cores, FBGs with different resonant wavelengths can be written simultaneously into the multiple cores in only one process with the scanned phase mask method. The MCF we used has a center core and six identical outer cores located respectively at the corners of a regular hexagon. The refractive index of the center core is a little lower than that of the outer cores. Due to the refractive index difference between the center core and outer cores, the FBGs with obviously different central wavelengths can be measured by only splicing a segment of a multimode fiber (MMF) between the MCF and the lead-in single mode fiber (SMF). The curvature sensitivity of the FBG in the outer core depends on the bending orientation in the form of a sine function. The maximum linear curvature sensitivity is about 0.128 nm/m-1. The proposed sensor offers advantages of flexibility in fabrication, simple interrogation, and capability of eliminating the cross-sensitivity to temperature or externally applied axial strain. The second one is a highly sensitive strain sensor based on a helical structure (HS) fabricated in the MCF. The MCF was locally twisted into an HS permanently by a CO2 laser splicing system and then spliced between two short sections of MMFs to construct an in-line Mach-Zehnder interferometer. In the region of the HS, the outer cores were deformed into helical cores while the center core was kept straight. Due to the HS, a maximum strain sensitivity as high as −61.8pm/με was experimentally achieved. It is the highest sensitivity among interferometer-based strain sensors reported so far, to the best of our knowledge. Moreover, the proposed sensor has the ability to discriminate axial strain and temperature, and offers several advantages such as repeatability of fabrication, robust structure, and compact size, which further benefits its practical sensing applications. Based on the MCF with the HS, we also propose and demonstrate a sensor for directional torsion and temperature discrimination. By introducing the short HS, the fiber circular asymmetry was achieved, which made the sensor have the ability of twist direction discrimination. The maximum torsion sensitivity of the proposed sensor reaches −0.118 nm/(rad/m) for the twist range from −17.094 rad/m to 15.669 rad/m. Compared with the previously reported torsion sensor schemes utilizing micro-machining means, the proposed sensor not only owns the capability of the discrimination of directional torsion and temperature but also takes the merits of easy fabrication and good mechanical robustness.